Bentuk a/b: Sebagai pecahan, pembagian, atau perbandingan? - Muhammad Irfan (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2017)
Understanding of a/b form is very important as the basis of proportional reasoning. This study discusses the interference of students thinking in understanding a/b form. This research uses qualitative research type with research subject of the prospective teacher of the second semester. The results of the study found that subjects experienced interference about the a/b form as a fraction, which should be as a form of comparison. Knowledge of fractions disturbs comparative knowledge, so the subject is wrong in understanding the a/b form. In addition, the subjects did not understand the simplification of distribution.